1986
DOI: 10.1051/rphysap:0198600210101100
|View full text |Cite
|
Sign up to set email alerts
|

Etude du mélange PVDF-PTMA

Abstract: 2014 On montre par analyse thermique différentielle, et par diffusion des rayons X aux petits angles que le fluorure de polyvinylidène et le polytétraméthylène adipate (PTMA) sont partiellement miscibles. Dans les alliages à base de PVDF peu concentrés, une faible concentration c ~ 2 % de PTMA modifie de manière très importante la microstructure lamellaire, et joue le rôle de plastifiant. Les propriétés mécaniques de ces alliages sont étudiées.Abstract. 2014 It is shown by DTA, WAXS and SAXS analysis, that po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This improvement in ductility with lignin addition can be attributed to both lignin plasticization effect and miscible blending between PA6 and lignin. Such a behavior has already been observed for partially miscible blend of polyvinylidene fluoride and polytetramethylene adipate . According to the authors small concentrations of polyester modify the lamellar microstructure and act as a plasticizer.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…This improvement in ductility with lignin addition can be attributed to both lignin plasticization effect and miscible blending between PA6 and lignin. Such a behavior has already been observed for partially miscible blend of polyvinylidene fluoride and polytetramethylene adipate . According to the authors small concentrations of polyester modify the lamellar microstructure and act as a plasticizer.…”
Section: Resultsmentioning
confidence: 67%
“…Such a behavior has already been observed for partially miscible blend of polyvinylidene fluoride and polytetramethylene adipate. 63 According to the authors small concentrations of polyester modify the lamellar microstructure and act as a plasticizer. Sailaja et al have demonstrated the same effect in a compatibilized composite of polyethylene and modified lignin via an esterified route.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…According to this (a) E-mail: Leizhang20@gmail.com model, the nanoscale phase separation is related to the hydrogen bonding and size-dependent surface tension intimately. Consequently, we expect that this intrinsic nanoscale behavior will appear in other miscible polymer blends with interphase interactions, such as hydrogen bonding and strong electrostatic interactions [13][14][15].…”
mentioning
confidence: 99%